Analysis of the Judge's Decision in Determining Custody Rights of Minors After Divorce: Study of Decision Number 708/Pdt.G/2025/PA.Skh at the Sukoharjo Religious Court - Muhammad Fajrul Minan; Baehaqi Baehaqi; Salman Salman; Aditya Fajri Kurnia Pradana; Muhammad Kurniawan Budi Wibowo; Jeong Chun Phuoc (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2026)
This study aims to analyze in-depth the judge's juridical considerations in granting custody of a minor child to the biological father in Decision Number 708/Pdt.G/2025/PA.Skh. The primary focus is to evaluate the consistency of the decision with the principle of